Can social media influencer (SMI) power influence consumer brand attitudes? The mediating role of perceived SMI credibility - Lubna Nafees; Christy M. Cook; Atanas Nikolov; James Stoddard (Digital Business, 2021)
Social media usage is pervasive, and brands must manage this channel carefully in order to meet their strategic goals. The role of social media influencers (SMI) is progressively becoming crucial for shaping consumer brand attitudes toward the firms' offerings. The purpose of this study is to empirically examine how SMIs can help brands build favorable brand attitudes and thus improve product acceptance and downstream business performance. Building upon naïve theory, consumer socialization theory and market signaling theory, we suggest that SMI power and SMI perceived source credibility are crucial in influencing consumer attitudes toward the brand. Using rich survey data from 231 U.S. social media users on Instagram the research employs confirmatory factor analysis (CFA) to access the psychometric properties of the measures and path analysis to test the proposed hypotheses. Results indicate that while SMI power is positively related to consumer attitudes toward the brand and perceived SMI expertise and trustworthiness partially mediate that relationship. This study contributes to extant literature by demonstrating that SMIs' role in shaping consumer attitudes toward the brand is a multilevel function of SMI power, partially mediated through SMI expertise and trustworthiness. Therefore, it is incumbent on brands to pay close attention to their SMI promotional channel.
Keywords: 650; Influencer marketing; Instagram; Perceived social media influencer expertise; Perceived social media influencer trustworthiness; Brand attitudes